BOOK REVIEWS (Journal of Finance, 1979)
Book reviewed in this article: CORPORATE FINANCE: Fundamentals of Financial Management . By EUGENE F. BRIGHAM. INVESTMENTS: Investment Analysis and Portfolio Management . By FRANK K. REILLY. INTERNATIONAL FINANCE: Anatomy and Consequences of Exchange Control Regimes . By JAGDISH BHAGWATI. MONETARY POLICY: Inflation and the Money Supply in the United States, 1956–1977 . By PETER I. BERMAN. BANKING: Managing Commercial Bank Funds . By EMMANUEL N. ROUSSAKIS. MISCELLANEOUS: Issues in Financial Regulation . By FRANKLIN R. EDWARDS. New Challenges To The Role Of Profit . Edited by BENJAMIN M. FRIEDMAN. Breadth and Depth in Economics: Fritz Machlup–The Man and His Ideas . By JACOB S. DRYER (Ed.).